SISTEM CASH DAN MEMBER GET MEMBER PADA PENGGUNA APLIKASI SNACK VIDEO SEBAGAI SUMBER INCOME PENDAPATAN: SISTEM CASH DAN MEMBER GET MEMBER PADA PENGGUNA APLIKASI SNACK VIDEO SEBAGAI SUMBER INCOME PENDAPATAN - Anggraini, Yessy Tri; Atika, Atika; Himsyah, Fatroyah Ars (Al-muamalah, 2023)
Snack Video is a short video social platform for all users to record and share their life, with the core mission of “Capture the World, Share Your Story”. The Member Get Member System in the Snack Video application is another way to make money through the snack video application by inviting and registering friends, then users who invite friends via the invitation code will receive money worth IDR 52,600 (can be adjusted according to promos). From snack video) in cash. This study uses a type of field research (field research). Data collected in this study through interviews, and directly to the object of research, and literature study using documentation from several literature books related to research. Primary data from this thesis were obtained through data obtained directly from the field through the results of interviews with informants related to the research. Secondary data was obtained by means of literature studies such as documentation from primary books which were considered representative of the research, and were also supported by secondary and thesis books as a complement to the existing primary books. And the data analysis used is a qualitative descriptive method using inductive thinking methods, namely studying a specific phenomenon that exists in the field to obtain its rules. Based on this research, it can be concluded that (1) Snack Video is a short video social platform where all users can record and share their lives, with missions completed and users get lots of coins collected from these missions. One of them is the Member Get Member System in the Snack Video application which is another way to make money through the snack video application by inviting and registering friends, then users who invite friends via the invitation code will receive money worth IDR 52,600 (can be adjusted according to promo from snack video) in cash. (2) The cash and Member Get Member system for snack video application users as income / income in the perspective of Sharia Economic Law uses the Ju’ālah contract because the video snack application pays users after the user has carried out the mission in the application by giving a predetermined number of points from each mission in the video snack application which in general have fulfilled the conditions and pillars and have been based on principles and principles in Sharia Economic Law, in accordance with Islamic law. Keywords: Snack Video, Cash System and Member Get Member, Akad, Ju’ālah